2013
DOI: 10.2172/1108160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Fields on Fish and Invertebrates Task 2.1.3: Effects on Aquatic Organisms Fiscal Year 2012 Progress Report Environmental Effects of Marine and Hydrokinetic Energy

Abstract: Energy generated by the world's oceans and rivers offers the potential to make substantial contributions to the domestic and global renewable energy supply. However, the marine and hydrokinetic (MHK) energy industry faces challenges related to siting, permitting, construction, and operation of pilotand commercial-scale facilities. One of the challenges is to understand the potential effects to marine organisms from electromagnetic fields, which are produced as a by-product of transmitting power from offshore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(47 reference statements)
0
9
0
2
Order By: Relevance
“…In contrast,Woodruff et al, 2013 found no significant effect of magnetic exposure on the activity rhythm (i.e., frequency of changes between stationary and active behaviours) of the Dungeness crab (M. magister) after 72 h of exposure to a magnetic field gradient (1100 µT DC decaying to approximately 330 µT). Similarly, Scott et al (2018) did not detect any modification of the time spent in movement under a 3 mT exposure (7 h) for juveniles of the edible crab (C. pagurus).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast,Woodruff et al, 2013 found no significant effect of magnetic exposure on the activity rhythm (i.e., frequency of changes between stationary and active behaviours) of the Dungeness crab (M. magister) after 72 h of exposure to a magnetic field gradient (1100 µT DC decaying to approximately 330 µT). Similarly, Scott et al (2018) did not detect any modification of the time spent in movement under a 3 mT exposure (7 h) for juveniles of the edible crab (C. pagurus).…”
mentioning
confidence: 73%
“…Supporting these results, Bochert and Zettler (2006) found no changes in the spatial distribution of the North Sea prawn (Crangon crangon), the isopod (Saduria entomon), the round crab (Rhithropanopeus harrisii), and the common starfish (Asturia rubens) in response to the unilateral magnetic field exposure of their tank (2.8 mT DC for 1.5 h). Likewise, neither the Dungeness crab (M. magister) nor the American lobster (Homarus americanus) modified their use of space after exposure to a magnetic field gradient (single Helmholtz coil located centrally and producing a maximal DC magnetic field of 1.01 mT, decaying to 0.05 mT at both ends of the tank, over 24 h) (Woodruff et al, 2013(Woodruff et al, , 2012. In a similar design (i.e AC and DC magnetic field gradients with a maximal intensity of 200 µT decaying to GMF values), juvenile European lobsters (Homarus gammarus) did not alter neither their exploratory behaviour (defined by mean velocity, total distance travelled and activity ratio) nor their shelter seeking behaviour (i.e time to find shelter, time spent in exposed vs control shelter) compared to control individuals (Taormina et al, 2020).…”
Section: Assessing Attraction or Repulsion Towards Artificial Magnetimentioning
confidence: 99%
“…• Laboratory studies have shown that exposure to EMFs of 3 milli Teslas has documented impact on a number of marine species, including Atlantic halibut, rainbow trout eggs, and coho salmon. It should be noted that 3 milli Teslas EMF levels are much higher that what would be expected for the deployment of single-unit or small-array MHK systems (Woodruff et al 2013).…”
Section: Known Knownsmentioning
confidence: 95%
“…• Behavioral responses, such as attraction to EMFs from subsea electric transmission cables, have been demonstrated through limited field and lab studies, but extrapolation to impacts of marine renewable energy power cables on critical behaviors of sensitive species or their populations would be speculative (Öhman, Sigray, and Westerberg 2007;Woodruff et al 2013;Gill et al 2014).…”
Section: Known Knownsmentioning
confidence: 99%
See 1 more Smart Citation